Clinical performance of long-span zirconia frameworks for fixed dental prostheses: 5-year results - Schmitter, Marc; Mußotter, Katrin; Rammelsberg, Peter; Gabbert, Olaf; Ohlmann, Brigitte (Journal of oral rehabilitation, 2012)
The purpose of this prospective cohort study was to assess the performance of tooth-supported, long-span, zirconia fixed dental prostheses (FDPs). Thirty FDPs with span lengths from 36 to 46 mm (mean 40·33 mm), with 4-7 units and with connector dimensions ∼9 mm2 were inserted (19 in the posterior region, 11 including anterior teeth) using glass-ionomer cement. The performance of the FDPs was assessed (aesthetic evaluation, failures, hypersensitivity/tooth vitality, secondary caries, pocket depth, decementation, and chipping) at baseline and after 5 years. Cox regression analysis was performed to identify risk factors. There were 16 failures after 5 years. Framework fracture occurred for two FDPs, four FDPs had to be re-cemented, one abutment tooth had to be treated endodontically, one abutment tooth fractured and cohesive failure of the veneer occurred for eight. Four FDPs had to be replaced, so survival was 82%. The aesthetics were rated as excellent by the patients at baseline and good at the 5-year recall. Cox regression analysis showed that both length [P = 0·05, exp(B) = 1·22] and location [P = 0·019, exp(B) = 4·09] of the FDP were risk factors for failure. Compared with the previously published 2-year results, the incidence of complications increased dramatically. Additionally, it was shown that long-span FDPs in the molar region are at greater risk of failure than FDPs in the anterior region.